High-density lipoprotein cholesterol, coronary artery disease, and cardiovascular mortality - Silbernagel, Günther; Schöttker, Ben; Appelbaum, Sebastian; Scharnagl, Hubert; Kleber, Marcus E.; Grammer, Tanja B.; Ritsch, Andreas; Mons, Ute; Holleczek, Bernd; Goliasch, Georg; Niessner, Alexander; Boehm, Bernhard O.; et al. (European heart journal, 2013)
High-density lipoprotein (HDL) cholesterol is a strong predictor of cardiovascular mortality. This work aimed to investigate whether the presence of coronary artery disease (CAD) impacts on its predictive value.We studied 3141 participants (2191 males, 950 females) of the LUdwigshafen RIsk and Cardiovascular health (LURIC) study. They had a mean ± standard deviation age of 62.6 ± 10.6 years, body mass index of 27.5 ± 4.1 kg/m², and HDL cholesterol of 38.9 ± 10.8 mg/dL. The cohort consisted of 699 people without CAD, 1515 patients with stable CAD, and 927 patients with unstable CAD. The participants were prospectively followed for cardiovascular mortality over a median (inter-quartile range) period of 9.9 (8.7-10.7) years. A total of 590 participants died from cardiovascular diseases. High-density lipoprotein cholesterol by tertiles was inversely related to cardiovascular mortality in the entire cohort (P = 0.009). There was significant interaction between HDL cholesterol and CAD in predicting the outcome (P = 0.007). In stratified analyses, HDL cholesterol was strongly associated with cardiovascular mortality in people without CAD [3rd vs. 1st tertile: HR (95% CI) = 0.37 (0.18-0.74), P = 0.005], but not in patients with stable [3rd vs. 1st tertile: HR (95% CI) = 0.81 (0.61-1.09), P = 0.159] and unstable [3rd vs. 1st tertile: HR (95% CI) = 0.91 (0.59-1.41), P = 0.675] CAD. These results were replicated by analyses in 3413 participants of the AtheroGene cohort and 5738 participants of the ESTHER cohort, and by a meta-analysis comprising all three cohorts.The inverse relationship of HDL cholesterol with cardiovascular mortality is weakened in patients with CAD. The usefulness of considering HDL cholesterol for cardiovascular risk stratification seems limited in such patients.
Published: 07 September 2013
Gesehen am 27.01.2022